Synthesis of zeolites from fly ash with the use of modified two-step hydrothermal method and preliminary SO sorption tests - Natalia Czuma; Paweł Baran; Wojciech Franus; Piotr Zabierowski; Katarzyna Zarębska (Adsorption Science & Technology)
Synthesis of zeolites from fly ash is an ecologically justified process aimed at the transformation of energy sector waste – fly ash into microcrystalline zeolites of broad possible application field. In this study, the synthesis of zeolites from fly ash by using a modified two-step synthesis was presented. The aim of such a planned experiment was to use the waste solutions from previous synthesis, in such a way that minimalization of negative influence of post-synthesis wastes on environment was possible. Received materials were tested for its sulfur dioxide sorption capacity, indicating its future possible application to capture SO2 from exhaust gases.